2018
DOI: 10.1007/978-3-319-94749-5_3
|View full text |Cite
|
Sign up to set email alerts
|

The “Inner Belief” of French Asylum Judges

Abstract: The judges of the French Court of Asylum, in charge of examining the cases of asylum seekers rejected by the French Office for the Protection of Refugees and Stateless Persons, affirm that there are very few technical legal aspects involved in asylum proceedings. They argue that the case law is not consistent and that the domestic law provides a vague definition of who is a refugee. Aside from these legal points, judges examine the “sincerity” of the applicant’s narrative as well as his or her attitude during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Many factors may influence judges' decision-making, such as culture, socialization, race, attitudes, cognition, emotion, or policy preferences (epstein and Knight 1998;Herlihy and Turner 2013;Maroney 2013). While much of the refugee studies literature consequently laments a certain level of arbitrariness regarding judges' decisions (e.g., Gill and Good 2019;Kobelinsky 2014Kobelinsky , 2015Kobelinsky , 2019, others have found that judges are also constrained by systemic and political pressures (Büchsel 2020). In what follows, it is important to take into account the tension between both judges' discretion in evaluating evidence and the systemic pressures under which they arrive at their decisions.…”
Section: Judges and Decision-makingmentioning
confidence: 99%
“…Many factors may influence judges' decision-making, such as culture, socialization, race, attitudes, cognition, emotion, or policy preferences (epstein and Knight 1998;Herlihy and Turner 2013;Maroney 2013). While much of the refugee studies literature consequently laments a certain level of arbitrariness regarding judges' decisions (e.g., Gill and Good 2019;Kobelinsky 2014Kobelinsky , 2015Kobelinsky , 2019, others have found that judges are also constrained by systemic and political pressures (Büchsel 2020). In what follows, it is important to take into account the tension between both judges' discretion in evaluating evidence and the systemic pressures under which they arrive at their decisions.…”
Section: Judges and Decision-makingmentioning
confidence: 99%
“…The symbolic meaning of a small body can lead to protective measures as young people may be positioned differently in the moral order, where physical immaturity induces sentiments and protectionism (Ursin, 2016). This also reveals how professionals’ perceptions of the body can be more decisive in assessments than the applicants’ statements (Kobelinsky, 2019).…”
Section: When Bodies Become Sites Of Evidencementioning
confidence: 98%
“…When evaluated, their first-hand accounts of vulnerability are by default considered subjective in the sense of being susceptible to selfseeking bias (e.g. Kobelinsky, 2019;Wettergren and Wikström, 2014). Even when given value as evidence, asylum seekers' accounts are firmly bound with the remembering and witnessing lived body that comes to disclose the reasons for their persecution as directly experienced, then and there.…”
Section: Objectivizing and Subjectivizing Logics Of Governingmentioning
confidence: 99%
“…For the representatives of asylum institutions, it is decisive to be able to define the nature of their own and refugees' knowledge to fit the expectations of the asylum assessment and decision making. To this end, institutional knowledge is deemed objective and thus disembodied from context, while the refugees' knowledge is seen as subjective, embodied and based on their firsthand experiences only (Jensen, 2018;Kobelinsky, 2019;Kynsilehto and Puumala, 2015;Puumala and Kynsilehto, 2016). In this sense refugees' own speech may end up being the least convincing form of knowledge, always potentially corrupted by the endeavor to be recognized as a refugee (Fassin and d'Halluin, 2005;McGhee, 2000;Häkli et al, 2017).…”
Section: Embodied Encounters: Governing and Agencymentioning
confidence: 99%